Mediated intestinal immunity by GALT (Gut Associated Lymphoid Tissue) in inflammatory bowel disease (Research, Society and Development, 2024)
Gut-associated lymphoid tissue (GALT) plays a fundamental role in the process of pathogen recognition, communication and activation of the immune system. Its response depends on the inflammatory state experienced by the individual and also on intestinal microbial colonization, which can influence homeostasis conditions or even contribute to tolerance and immunological memory processes. However, the role of GALT in inflammatory bowel diseases (IBD) is not yet completely understood. IBD affects the gastrointestinal tract, promoting lack of control of the immune system, which starts attacking cells in the tissue itself, promoting tissue damage. In this sense, the main objective of this narrative review is to understand the role of GALT in IBD; identifying the role of the microbiota within this scenario. To this end, 35 scientific articles were selected, published in Portuguese and English, in the period from 2020 to 2024, in the Scholar, Scielo, Pubmed and Sciencedirect databases. The inflammatory state generated by the pathogenic microbiota can hyperstimulate the GALT, enhancing the emergence or even intensification of intestinal inflammatory diseases. In this sense, the use of prebiotics, probiotics, synbiotics and postbiotics can modulate the intestinal microbiota, promoting a less probiotic environment. inflammatory.